The Paradox of Nihil Punishment Regulation for Corruption as an Extraordinary Crime - Prima Hazairin Bakhtiar; Sodikin Sodikin (Fox Justi : Jurnal Ilmu Hukum, 2026)
The imposition of "nihil" (null) punishment on mega-corruption defendants, specifically in the Benny Tjokrosaputro case involving total losses of approximately Rp22 trillion, has sparked intense debate regarding the effectiveness of law enforcement and the public's sense of justice. As an extraordinary crime, corruption should be handled with extraordinary sentencing instruments. However, in practice, the Panel of Judges based the sentencing on Article 67 of the Criminal Code (KUHP), which is designed for ordinary crimes. Consequently, this research aims to analyze the juridical rationality of applying nihil punishment from a welfare state perspective and examine the implications of the legal vacuum within the Anti-Corruption Law (UU Tipikor) on the effectiveness of corruption eradication. Using normative legal research methods, the results indicate that nihil punishment creates a legal anomaly where extraordinary crimes are degraded to ordinary ones, thereby obscuring the dignity of the Anti-Corruption Law as lex specialis. This research proposes a revision of the Anti-Corruption Law by strengthening the extraordinary sentencing system, including the options of the death penalty, aggressive special fines, and the implementation of multiple life sentences to ensure no impunity or legal loopholes for repeat multi-case corruption perpetrators.